Protura (Hexapoda) from Doi Suthep-Pui National Park, Chiang Mai, Thailand - Nakamura, Osami; Likhitrakarn, Natdainai (Zootaxa, 2009)
Eight proturan species were collected from Doi Suthep-Pui National Park, northern Thailand. Among them, three species are new to science: Baculentulus chiangmaiensis, Kenyentulus suthepicus, and Eosentomon chiangmaiense. Baculentulus ogawai (Imadaté) is redescribed.